(untitled) (Scientific journal of the Fergana State University, 2026)
A new metal complex compound of the composition [NiC24H18O2N2] was synthesized by the interaction of 2-hydroxy-1-naphthaldehyde (2-hnaph), ethylenediamine (EDA), and NiSO4 with solutions in ethyl alcohol. The composition, molecular and crystalline structure of this metal complex compound were investigated using X-ray structural analysis (XRD). A reaction occurs between the oxygen of the carbonyl in the aldehyde form of 2-naph and the amino (NH2) groups of ethylenediamine, releasing one molecule of water (>C=O + -NH2 → >C=N- +H2O). The resulting new ligand is bound to the central atom by two oxygen atoms and two nitrogen atoms. The bond length of Ni1-O1 is 1.850 (3) Å, and the Ni1-N1 and Ni1-N2 bonds are bonded at a distance of 1.832 (4) and 1.838 (4) Å, respectively. The angles between the atoms O1 - Ni1-O1’ and O1 - Ni1-N1 are respectively 86.60 (16)0, 93.12 (16)0 and the parameters of the hydrogen bond are also given.